Favourite melodies of Asia and the Pacific [soundrecording]. (Japan Asian Cultural Centre for UNESCO, 1986)
A popular music in Asia and the Pacific promoting the rich cultural tradition through the most valuable language without frontier' - Music.
Afghanistan (Bibi shirinay) -- Australia (Lhambilbik ...) -- Bangladesh (Projapati projapati ...) -- Burma (Doh-bat than ...) -- China (Moli Hua ...) -- India (Odivileyadu pappa ni eyndi rukklagadu pappa) -- Indonesia (Senggot ...) -- Japan (Sakura sakura ...) -- Korea (Saeya saeya ...) -- Malaysia (Katak lompat ...) -- Mongolia (Instrumental ensemble ...) --Nepal (Basa basa re ...) -- New Zealand (Koauau ...) -- Pakistan (Sonhi dharti ...) -- Papua New Guinea (Malu baidam) -- Philippines (Pamulinawen ...) -- Sri Lanka (Nelum varuna) -- Thailand (Chaang ...) -- Vietnam (Tro ve tay nguyen ...).
Special selection edition for school use from the Series of Asian/Pacific Music Materials Co-production Programme.
Sung in different language.
Keywords: Folk-songs, Asian; Folk-songs -- Pacific area; Folk-songs -- Philippines; Popular music -- Asia; Popular music -- Pacific area; Music